Sexually Dimorphic Behavioral and Genetic Outcomes Associated With Administration of TA65 (A Telomerase Activator) Following Repetitive Traumatic Brain Injury: A Pilot Study - Eyolfson, Eric; Malik, Haris; Mychasiuk, Richelle (Frontiers in Neurology, 2020)
Children and adolescents have the highest rates of traumatic brain injury (TBI), with mild TBI (mTBI) accounting for most of these injuries. This demographic also often suffers from post-injury symptomologies that may persist for months. Telomere length (TL) has previously been used as a marker for outcomes following repetitive mild TBI (RmTBI) and it may be possible that telomere elongation can reduce post-traumatic behavioral impairments. Telomerase activator-65 (TA-65) is a telomerase small-molecule activator purified from the root of Chinese herbs that has been anecdotally reported to have anti-aging and life-extending potential. We hypothesized that RmTBI would shorten TL but administration of TA-65 would reverse RmTBI-induced telomere shortening and behavioral deficits. Male and female Sprague-Dawley rats were orally administered TA-65 or a placebo substance for 30 consecutive days [postnatal day (P) 25–55]. Following the injury protocol (mTBIs on P33, 36, and 40), rats went through a behavioral test battery designed to examine symptomologies commonly associated with mTBI (balance and motor coordination, exploratory behavior, short-term working memory, and anxiety- and depressive-like behaviors). TL in ear and brain tissue (prefrontal cortex and hippocampus) and relative expression of TERT and Tep1 via qPCR were assessed 15 days following the last injury. We observed a heterogenous response between males and females, with TA65 administration resulting in increased mRNA expression of TERT and Tep1 in female rats that experienced RmTBI, which was accompanied by some functional recovery on motor behavior and footslips in the beam walk task and depressive-like behavior in the forced swim task.